Assessment of environmental impacts and environmental protection in Block 05-2 & 05-3, Nam Con Son basin - Do Thi Quynh Trang; Dang Anh Tuan; Le Quoc Thang (Petrovietnam Journal, 2019)
The paper analyses and assesses the quality of seawater, sediment and benthic community in the area of Hai Thach - Moc Tinh fields, Nam Con Son basin during the 2009 - 2018 period. Environmental monitoring data showed that the content of total hydrocarbon (THC) and barium (Ba - indicating the pollution of drilling cuttings) might fluctuate in a variety of scales and intensities. The impact of THC is within a radius of 500m; Ba varies within a range of about 1,000m (some stations within 2,000m) from the discharged point. The environment impacts decrease after the end of drilling operation, the level of environmental rehabilitation depends on thesediment environment and topography at reservoir of production area, the drilling mud system used, the amount of drilling cuttings and produced water discharged. In case of synthetic-based mud used, after the drilling campaign is over from 2 to 3 years, pollution indicators such as THC and Hs have been recovered in comparison with obtained data of baseline survey in 2009.